2017
DOI: 10.1371/journal.pone.0185765
|View full text |Cite
|
Sign up to set email alerts
|

Fast hyperbaric decompression after heliox saturation altered the brain proteome in rats

Abstract: Better understanding of the physiological mechanisms and neurological symptoms involved in the development of decompression sickness could contribute to improvements of diving procedures. The main objective of the present study was to determine effects on the brain proteome of fast decompression (1 bar/20 s) compared to controls (1 bar/10 min) after heliox saturation diving, using rats in a model system. The protein S100B, considered a biomarker for brain injury, was not significantly different in serum sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…This suggests endothelial dysfunction at early age of ApoE KO rats although this was not studied yet. In comparative studies that simulate human diving, rats have been used more than any other species (Lillo et al, 1985; Lillo and Parker, 2000; Bjorkum et al, 2017). In compressed gas diving, the pulmonary vasculature is exposed to oxidative stress and oxygen toxicity due to high partial pressure of oxygen and inert gas bubbles that develop during the decompression (ascent) phase (Butler and Hills, 1979; Wingelaar et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests endothelial dysfunction at early age of ApoE KO rats although this was not studied yet. In comparative studies that simulate human diving, rats have been used more than any other species (Lillo et al, 1985; Lillo and Parker, 2000; Bjorkum et al, 2017). In compressed gas diving, the pulmonary vasculature is exposed to oxidative stress and oxygen toxicity due to high partial pressure of oxygen and inert gas bubbles that develop during the decompression (ascent) phase (Butler and Hills, 1979; Wingelaar et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…While a prolonged exposure to hyperoxia may decrease 20S proteasome activity and increase levels of apoptotic proteins ( 32 ), short repetitive hyperbaric oxygenation might generate opposite results, leading to a conditioning effect. It has been also shown that modulating pressure conditions may affect proteasome expression as hyperbaric decompression upregulates proteasome subunit beta type-7 in the rat brain ( 33 ). Future studies will examine whether and how HBO preferentially targets the apoptotic protein for degradation as suggested by this present study.…”
Section: Discussionmentioning
confidence: 99%